Is Adjuvant Chemotherapy Necessary for Obstructing Stage II Colon Cancer? Results From a Propensity Score Analysis of the French Surgical Association Database. Issue 1 (January 2022) - Sabbagh, Charles; Manceau, Gilles; Mege, Diane; Abdalla, Solafah; Voron, Thibault; Bridoux, Valérie; Lakkis, Zaher; Venara, Aurélien; Beyer-Berjot, Laura; Diouf, Momar; Karoui, Mehdi
Abstract : Objective: The aim of this study was to compare the survival of patients with stage II obstructing colon cancer (OCC) who had adjuvant chemotherapy with those who did not. Summary Background Data: The need for adjuvant chemotherapy in stage II colon cancer is still debated. Methods: All consecutive patients treated for a stage II OCC in a curative intent (with primary tumor resection) between January 2000 and December 2015 were included in this retrospective, multicenter cohort study which included a propensity score analysis using an odds of treatment weighting (Average Treatment effect on the Treated, ATT). The endpoint was the comparison between the 2 groups for overall survival (OS) and disease-free survival (DFS) according to whether or not patients received adjuvant chemotherapy. Results: During the study period, 504 patients underwent a curative colectomy for a stage II OCC. Among these patients, 179 (35.5%) had adjuvant chemotherapy and 325 (64.5%) had no adjuvant treatment. Among the 179 patients who received adjuvant chemotherapy, 108 patients (60%) received oxaliplatin based regimen and 99 patients (55%) completed all scheduled cycles. At multivariate analysis, after weighting by the odds (ATT analysis) and adjustment, adjuvant chemotherapy after resection of a stage II OCC was associated with improvements in OS [hazard ratio (HR) = 0.42 (0.17–0.99), P = 0.0498] and DFS [HR = 0.57 (0.37–0.88), P = 0.0116]. Conclusion: This study suggests that adjuvant chemotherapy after curative resection of stage II OCC may improve oncological outcomes.